A Suggested Scenario to Raise the Efficiency of Electronic Academic Counseling in the college of Shari’a and Islamic Studies، Al-Hasa - Imam Mohammad Ibn Saud Islamic University: تصور مقترح لرفع كفاءة الإرشاد الأكاديمي الإلكتروني بكلية الشريعة والدراسات الإسلامية بالإحساء، جامعة الإمام محمد بن سعود الإسلامية - Saad Mamoun AbdelRahman Abu Alwan, Omer Ahmed Elmustafa Hayati (Journal of engineering sciences and information technology, 2020)
This research aims at developing a proposed vision to raise the efficiency of electronic academic advising at the College of Sharia and Islamic Studies in Al-Ahsa, at the Imam Muhammad bin Saud Islamic University. And to design a computer system for the academic advisor, that facilitates his performance in an advanced electronic environment. The research questions are: What is the reality of the electronic academic guidance in the college? and what is the proposed perception to raise its efficiency?. The methodology adopted in this research is based on case study method, and the information gathered by a group interview conducted with the Academic Advising Unit members in the college, and other individual ones with the Academic Advising Committees members at the departmental level. Other information was collected from specialized books, scientific research and websites. The research main results show the fact that Collage administration pays the academic guidance process a special interest, sets plans, trains advisors and disseminate academic advising, such as students’ rights and duties, via the college website, lectures and pamphlets. And succeeded in some tasks related to academic excellent and weak students. However, the academic advising operation in the Collage suffers from some problems, the most important of which is the lack of eligibility of the academic advisor to enter the system, and thus affected negatively the whole advisory process. To solve these problems, a "smart electronic assistant for the academic advisor" computer system was designed, which It is linked to the admission and registration system and enables the academic advisors to enter the system and help them in managing their advisory mission in an accurate, up to date and fast electronic way. And according to the quality standards of The National Center for Academic Accreditation and Evaluation in the Kingdom of Saudi Arabia. The researchers recommended that, the necessity of developing electronic academic advising systems and establishing electronic academic advising management systems (AMS) similar to the electronic learning management systems (LMS).